Emergency Medicine/Internal Medicine Combined Residency Graduates Have High Career Satisfaction and Commonly Practice in Both Specialties. Issue 2 (24th July 2020) - Scott, Nathaniel; Rodos, Adam; Dwyer, Ryan; Tyo, Carissa; Martin, Daniel
Abstract: Objectives: The first combined emergency medicine/internal medicine (EM/IM) residency was established in 1991. As the 30th anniversary of this unique dual‐training opportunity approaches, multiple changes to the practice and educational landscape have occurred. Previous surveys examining this topic are now more than 10 years old and occurred prior to the establishment of the EM/IM/critical care medicine (EM/IM/CCM) pathway. We conducted a survey to investigate career trajectories, satisfaction, and opportunities available to EM/IM graduates. Methods: Survey questions were developed to both allow for comparison with previously published data and examine new topics not previously investigated. A group of EM/IM and EM/IM/CCM program directors validated the survey questions. Eligible respondents were identified and contacted through their previous residency program leadership. Results: Fifty‐two percent (152/290) of graduates completed the survey. Thirty‐seven percent of respondents practice both EM and IM, 51% practice EM only, and the remainder practice IM only. Thirty‐one percent of total respondents completed a fellowship, with critical care being the most popular choice. Seventy‐one percent of graduates practice in an academic center, and many hold leadership positions within education, research, and hospital administration. Eighty‐seven percent of graduates were "extremely satisfied" with their choice to pursue EM/IM or EM/IM/CCM and 95% reported that they would choose this path again. Conclusions: Most respondents are satisfied with their residency choice and would choose to pursue this training again, despite the additional years of training. The proportion of graduates pursuing fellowship is higher than previously published data. Most continue to work in academics, and many are leaders within their institutions. The changing health care landscape offers multiple opportunities to dually trained graduates.